Sustainable value to the customer through the relationship between quality and marketing - Al–Qaysi, Bilal jasim; abdul – kareem, Fa,aizah (Opción, 2019)
The purpose of this study is to present the perspective built on both overall quality management and relationship marketing via different methods such as the experimental approach and statistical analyses. The current research revealed that overall quality management and its dimensions (i.e. management leadership, workers’ participation, kaizen, workers training) support the process of customer loyalty; however, they do not improve this process. As a conclusion, the key to the success of insurance companies is the leadership thought which leads the company towards success in a competitive environment in the insurance sector.